2013
DOI: 10.1186/2050-6511-14-62
|View full text |Cite
|
Sign up to set email alerts
|

Ecotoxicology inside the gut: impact of heavy metals on the mouse microbiome

Abstract: BackgroundThe gut microbiota is critical for intestinal homeostasis. Recent studies have revealed the links between different types of dysbiosis and diseases inside and outside the intestine. Environmental exposure to pollutants (such as heavy metals) can also impair various physiological functions for good health. Here, we studied the impact of up to 8 weeks of oral lead and cadmium ingestion on the composition of the murine intestinal microbiome.ResultsPyrosequencing of 16S RNA sequences revealed minor but s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
120
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(133 citation statements)
references
References 30 publications
(33 reference statements)
9
120
4
Order By: Relevance
“…The gastrointestinal tract absorbs a small part of cadmium, and a majority of cadmium remain in the intestinal mucosa (Andersen et al 1988). Breton et al found that non-absorbed cadmium had a direct impact on mouse gut microbiota and in turn impact the alimentary tract and overall gut homeostasis (Breton et al 2013). For these reasons, we conjectured that cadmium exposure may lead to loss of weight due to impaired absorption function of gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 95%
“…The gastrointestinal tract absorbs a small part of cadmium, and a majority of cadmium remain in the intestinal mucosa (Andersen et al 1988). Breton et al found that non-absorbed cadmium had a direct impact on mouse gut microbiota and in turn impact the alimentary tract and overall gut homeostasis (Breton et al 2013). For these reasons, we conjectured that cadmium exposure may lead to loss of weight due to impaired absorption function of gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 95%
“…72 Other studies, 454 using higher doses than ours, reported oral Pb exposure effects on the gut microbiota 455 composition mediated by non-absorbed heavy metals or before their absorption. 73 In Pb 456 exposed partridges, the high concentration of Pb in the intestine several weeks after 457 exposure and Pb effects on constitutive immunity are both likely mechanisms 458 explaining observed changes in the gut bacteria. 459…”
Section: Nabs Enhance Antigen Presentation and Initiate Specific Respmentioning
confidence: 98%
“…There are relatively few studies that examine the role of environmental contaminants on the human microbiome or in model systems (10)(11)(12) and even fewer that address this in wildlife. One such study indicates that arsenic exposure in drinking water can alter the composition of gut microbiota in mice and the subsequent suite of metabolites produced by the microbes, thereby potentially altering the function of this complex symbiotic community (11).…”
mentioning
confidence: 99%